2018
DOI: 10.1002/jctb.5847
|View full text |Cite
|
Sign up to set email alerts
|

Starmerella bombicola: recent advances on sophorolipid production and prospects of waste stream utilization

Abstract: Sophorolipids are among the most extensively studied microbial biosurfactants. Starmerella bombicola is the most productive strain known for sophorolipid production, with volumetric productivity of up to 3.7 g L−1 h−1. This review focuses on the two most important aspects that have an influence on sophorolipid commercialization. Firstly, the metabolic engineering achievements of S. bombicola in the last decade are summarized. Secondly, three improvements of the bioprocess are described, including alternative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 57 publications
(93 reference statements)
0
27
0
4
Order By: Relevance
“…This goal can be achieved by adopting different strategies such as the use of cheaper renewable feedstocks or even waste materials as substrates (Jiménez‐Peñalver et al, ; Maddikeri et al, ), the use of novel or modified strains to improve production (Van Bogaert et al, , ), or the synthesis of modified SL with better biological and physicochemical properties than natural SL (Peng et al, ; Zhang et al, ). The fermentation and downstream strategies and bioreactor design also have a tremendous impact on productivity, and solid‐state fermentation shows an interesting potential, allowing for the use of solid insoluble wastes as substrates (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This goal can be achieved by adopting different strategies such as the use of cheaper renewable feedstocks or even waste materials as substrates (Jiménez‐Peñalver et al, ; Maddikeri et al, ), the use of novel or modified strains to improve production (Van Bogaert et al, , ), or the synthesis of modified SL with better biological and physicochemical properties than natural SL (Peng et al, ; Zhang et al, ). The fermentation and downstream strategies and bioreactor design also have a tremendous impact on productivity, and solid‐state fermentation shows an interesting potential, allowing for the use of solid insoluble wastes as substrates (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The yeasts recently reported for the production of biosurfactants include Candida sphaerica , 86 Starmerella bombicola , 87 C. lipolytica , 1 C. utilis , 61 Saccharomyces cerevisiae , 88,89 and Meyerozyma guilliermondii , 90 which have potential as producers of compounds with emulsification and surfactant activities as well as antimicrobial and antioxidant properties. Moreover, the recovery percentages are higher compared to the yields of emulsifiers derived from other microorganisms.…”
Section: Biosurfactantsmentioning
confidence: 99%
“…As with the sophorolipids, the productivities are lower than those observed in traditional production systems. However, it is expected that by devoting more effort to SSF optimization, both reactor design and control parameters, further improvements can be reached (Wang et al, 2018;El-Housseiny et al, 2019). Jimenez-Peñalver et al 2018also reported that there is a high influence of the substrates on the type and yield of sophorolipid produced.…”
Section: Product Developmentmentioning
confidence: 99%
“…Jimenez-Peñalver et al 2018also reported that there is a high influence of the substrates on the type and yield of sophorolipid produced. Therefore, there is a wide range of sophorolipids production yield ranging between 0.06 and 1.07 g g −1 DM using agroindustrial sugar and fat sources (Wang et al, 2018).…”
Section: Product Developmentmentioning
confidence: 99%